2012
DOI: 10.1309/ajcp8qdn7nauxjfj
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of New Automated Hepatitis B Viral Markers in the Clinical Laboratory

Abstract: We evaluated quantitative hepatitis B surface antigen (qHBsAg) assays and a hepatitis B virus (HBV) core-related antigen (HBcrAg) assay. A total of 529 serum samples from patients with hepatitis B were tested. HBsAg levels were determined by using the Elecsys (Roche Diagnostics, Indianapolis, IN) and Architect (Abbott Laboratories, Abbott Park, IL) qHBsAg assays. HBcrAg was measured by using Lumipulse HBcrAg assay (Fujirebio, Tokyo, Japan). Serum aminotransferases and HBV DNA were respectively quantified by us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 26 publications
0
9
0
1
Order By: Relevance
“…The variations in the correlation between HBsAg and HBV-DNA levels was attributed to differences in disease stage, HBeAg status, HBV genotypes involved, and types/phases of treatment (16,25) and should always be considered in HBV DNA and HBsAG level correlation studies. Even though most of these factors were not established in the current study, similar to the report by Ganji et al (9), this study highlights a significant insight into differences in HBsAg levels between HBeAg positive and negative patients, which appear to be affected by HBeAg status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The variations in the correlation between HBsAg and HBV-DNA levels was attributed to differences in disease stage, HBeAg status, HBV genotypes involved, and types/phases of treatment (16,25) and should always be considered in HBV DNA and HBsAG level correlation studies. Even though most of these factors were not established in the current study, similar to the report by Ganji et al (9), this study highlights a significant insight into differences in HBsAg levels between HBeAg positive and negative patients, which appear to be affected by HBeAg status.…”
Section: Discussionmentioning
confidence: 99%
“…Using the Lemeshow et al (15) formula for estimating population proportion with specified absolute precision, setting α at 0.05, and correlation rates of 34% (16) for HBsAg and HBV DNA levels, a total of 172 HBV patients were recruited to achieve 0.95 power and to obtain a total of 344 matched HBsAg and HBV DNA level tests. Consenting adult patients were enrolled in the study.…”
Section: Study Design and Settingmentioning
confidence: 99%
“…The most widely used is the Architect assay, but HBsAg quantification may also be performed using the Elecsys platform (HBsAg Quant Package Insert, Roche Diagnostics 2011) [15-17]. …”
Section: Hbv (Hepatitis B Virus)mentioning
confidence: 99%
“…A new assay was developed for measuring HBV core-related antigen (HBcrAg), which consists of a core, e antigen (HBeAg), and the precore HBV proteins (22-kD precore fragment, amino acids 28-150); HBcrAg levels correlated well with HBV DNA levels [15]. A recent study showed that the serum HBcrAg concentration was related to the level of intrahepatic cccDNA [16].…”
Section: Hbv (Hepatitis B Virus)mentioning
confidence: 99%
See 1 more Smart Citation